(untitled) (Medical Forum Monthly, 2024)
Objectives: (1) To assess frequency of burns injury in general population. (2) To assess the knowledge & practices of paramedical staff on burns cases. (3) To compare the knowledge & management of burn cases among paramedical staff at Jinnah Post Graduate Medical Center And Burns Ward Civil Hospital Karachi Study Design: Cross sectional study Place and Duration of Study: This study was conducted at two Tertiary Government Hospital that is Jinnah Post Graduate Medical Center and Burns Ward at Civil Hospital Karachi from February 2016 to October 2016. Materials and Methods: A cross sectional study was conducted on a sample size of 284 paramedics. The sample was taken through Non-probability purposive sampling from the above-named two tertiary government hospital. An informed verbal consent was taken from the paramedics. A pilot study was conducted to assess the validity of questionnaire. A structured questionnaire was distributed which was filled. Data was analyzed using SPSS version 21 with 95% confidence interval, margin of error was taken as 5% and P-value 0.05 was considered significant. Results: A study was done to check the knowledge and practice about burn injury between the paramedics of JPMC and Burns ward CHK. 81% data was collected from while 19 % from Burns ward CHK. When asked about the use of water after 30 min of burn injury, 70.40% (p = 0.001) paramedics of Burn ward said it isn’t beneficial while majority 55.20% JPMC paramedics said it is beneficial. Similarly 81.50% (p = 0.001) Burns ward CHK paramedics said icing helps burn injury compared to 57.80% of JPMC. Majority of Burns ward CHK paramedics 81.50% (p = 0.000) were familiar with the use of silver sulfadiazine cream in deep thickness burn compared to 46.10% JPMC paramedics. Regarding resuscitation in a complicated situation 88.90% (p = 0.005) Burns ward CHK paramedics acquainted compared to 70.40% JPMC paramedics. 79.60% (p = 0.005) Burns ward CHK paramedics said that they undergo with the removal of previous cream before applying new dressing compared to 59.10% JPMC paramedics while regarding the use of analgesic 90.70% (p = 0.002) Burns ward CHK paramedics give it compared to 70.40% JPMC paramedics. As far as extra nutrition for a burn patient, 88.90% (p = 0.003) Burns ward CHK were aware compared to 68.70% JPMC paramedics. When asked about development of bedsores in a burn patient 70.40% (p = 0.001) Burns ward CHK paramedics perceived compared to 45.20% JPMC paramedics. Conclusion: The study concluded, though all the paramedics are given the training of management of burns cases, Civil hospital paramedics are more competitive and have better knowledge and practices than JPMC paramedics.